Teachers' conceptualization of content and language integrated learning (CLIL): evidence from a trilingual context - Karabassova, Laura (International journal of bilingual education and bilingualism, 2022)
This paper reports on research into the top-down implementation of CLIL in the trilingual context of Kazakhstan, with a focus on teachers' conceptualization of integration. Kazakhstan is the first Central Asian country to introduce CLIL for using three different languages as a medium of instruction for different content subjects as part of an ambitious national language-in-education policy. With a constructivist position, the study sought to explore the reality, i.e. the conceptualization of CLIL from teachers' own perspectives through interviews and observations with five participants, working in the network of 20 state-funded and highly selective Nazarbayev Intellectual Schools. Findings suggest that most of the participating teachers were not aware of the pedagogical intentions behind CLIL and understood it merely as just teaching through another language. The subject teachers, who worked in the context of demanding enquiry-based curriculum, prioritized content over language, assuming only an indirect role in facilitating students' language development.